Geração automática de modelos geométricos de pontes e viadutos - Sousa, Ícaro Manfrinni Rodrigues (2021)
Structural design is a very important phase of building engineering structures. In this phase, 3D geometric models facilitate the verification of the geometric requirements of the structure being designed, such as bridges, where the complexity of the shape requires greater attention. This type of model, integrated with a 3D representation of the construction environment, allows the professionals to check conflicts with other models, and to analyze the aesthetic qualities of the bridge. In this sense, parametric modeling allows the construction of more dynamic and flexible models for possible future changes, being very attractive to the infrastructure area for presenting standardization in geometry, especially in roadways, bridges and tunnels. In this work, automated generation of box girder bridge models and visualization is presented. This type of cross-section is widely used because it provides high rigidity with little material consumption. Geometric parameters are defined from the combination of recommendations of current standards and design criteria adopted by designers. Two case studies were chosen for more details about the technique: an existing viaduct located in the downtown area of a city in Rio Grande do Norte (Brazil) and a fictitious bridge connecting two coastal cities. The main objective of this work is to assist the bridge designer, in the design phase of the project, allowing quick 3D visualization of the designed structure, speeding up decision making about the adopted structural solution for the bridge construction.